Circulating intercellular adhesion molecules in blood and bronchoalveolar lavage in Behçet's disease - A. Hamzaoui; K. Hamzaoui; A. Chabbou; K. Ayed (Hindawi Limited, 1995)
The aim of this study was to evaluate circulating intercellular adhesion molecule-1 (cICAM-1) in serum and in bronchoalveolar lavage (BAL), as a marker for the inflammatory process in patients with active Behçet's disease (BD). Circulating ICAM-1 was tested by an enzyme linked immuno-sorbent assay in serum and in BAL of patients with BD. These values were compared to those of patients with tuberculosis and to healthy controls. Increased levels of circulating ICAM-1 were found in serum from patients with active BD compared to healthy controls (p < 0.01). Similar levels of serum cICAM-1 were found in BD and tuberculosis. Additionally, both BD and tuberculosis patients exhibited high levels of cICAM-1 in BAL fluid, suggesting that this increase may be a result of the immune system activation in inflammatory sites. Circulating ICAM-1 seemed to have a good discriminative power in identifying active BD, being elevated in all active stages (p < 0.01) compared to remission BD stage. No differences were found in active BD patients depending upon the clinical manifestations. These results suggest that cICAM-1 may be involved in leucocyte adhesion and migration into the vessel wall of the lung. Circulating forms are derived from molecules expressed on the surface of activated cells, as a result of an inflammatory process.